Characteristics and Therapeutic Patterns of Hyperthyroidism in Eastern Indonesia: A Hospital-Based Study - Rahmatullah, Alif Rizki; Fadhila, Luthfiya Nur; Mussyafa, Aulia Putri; Wulandari, Inayah; Tunairin, Siti Raodatul Jannah; Gunawan, Aulya Khalisha; Nurmawaddah, Intan; Ningrum, Sania Tresna; Rahadian A., M. Fathir; Kusuma P, I Putu Aryana; Rifki, Muhammad (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Hyperthyroidism, a condition of excessive thyroid hormone production, presents significant diagnostic and management challenges worldwide. Its clinical spectrum is broad, influenced by etiology, patient demographics, and regional factors. This study was conducted to provide a detailed description of the clinical characteristics, demographic profile, and management patterns of hyperthyroid patients at Dr. (H.C) Ir. Soekarno Regional General Hospital, a tertiary care center in Bangka Belitung Province. This research utilized a descriptive observational method with a cross-sectional design. Data were retrospectively collected from the medical records of 83 patients diagnosed with hyperthyroidism between January and December 2024. The collected variables included age, gender, clinical manifestations, laboratory findings, and prescribed therapeutic regimens. The analysis revealed a significant female predominance (86.7%) among patients, with the majority falling into the >35 years age group (56.6%), confirming established epidemiological trends. The most prevalent clinical findings were palpitations (90.4%), goiter (85.5%), and unexplained weight loss (78.3%). Graves' disease was identified as the primary etiology in 72.3% of cases. The mainstay of treatment was pharmacotherapy, with Methimazole being the most frequently prescribed antithyroid drug (81.9%), often supplemented with beta-blockers (74.7%) for symptomatic control. This study concludes that the clinical profile of hyperthyroidism at this tertiary hospital aligns with classical presentations, predominantly affecting adult women. The findings underscore the importance of recognizing key symptoms for early diagnosis and affirm that current management practices are consistent with established clinical guidelines.